A Model Approach to Understanding Monetary Aggregates Growth in Sierra Leone and Implications for Policy Formulation - JACKSON, Emerson Abraham; VANDY, Patricia Sarah (Theoretical and Practical Research in Economic Fields; Vol 13 No 1 (2022): TPREF, Volume XIII, Issue 1(25), Summer 2022, 2022)
This study has adopted a model approach to developing an understanding of monetary aggregates (MA) growth in Sierra Leone, which certainly has implications for effective policy formulation by the central bank authority. In pursuance of this, we utilized the Autoregressive Moving Average (ARIMA) model with data spanning 2002M1 to 2021M12 to investigate the out-of-sample projection performance of the disaggregated components that makes up the MA for Sierra Leone – typically in this case Reserve Money (RMA), Currency-in-Circulation (CiC) and Reserve Money (RM). In our evidence from the empirical projection (covering the period 2022M1-2022M12), we observed that RM is projected to grow more than CiC over the observed period. Given RM being the operational target of the Bank of Sierra Leone, we believe that such an outcome is a promising indication particularly in ensuring the bank addresses its core mandates of monitoring price and financial stability. The increased scope of RM in the BSL system is a laudable outcome when it comes to meeting reserve requirements and also managing risks about price and financial stability. The study recommends that the BSL adopt innovation strategies concerned with FinTech and the emergence of the National Switch to effectively manage the MA portfolio in the entire banking system, which will also support the overall growth ambition of the central government.